"Who Am I to Question Them?" Pre-Service Teachers and Provisional Teacher Testing Policy under COVID-19. Issue 1 (2nd January 2022) - Hara, May
ABSTRACT: In this qualitative study, I examine a provisional teacher testing policy designed and implemented in response to the COVID-19 pandemic. Survey and focus data from a public teacher education program in Massachusetts in the spring of 2021 shows that provisional teacher testing policy eased financial, logistical, and emotional pressure for teacher candidates. In spite of the affordances of the provisional policy, many respondents supported a return to the pre-COVID-19 testing policy. Data point to a tension between respondents' view of the benefits of the provisional policy and the influence of powerful norms of individual responsibility, meritocracy, and compliance. Importantly, respondents described how changes due to the COVID-19 pandemic led to a broader view of what might be possible in teacher testing policy and pre-service teacher policy engagement as a whole. Using one case study, I offer recommendations for increasing professional policy training and more inclusive policy processes in teacher education.